2020
DOI: 10.1111/liv.14467
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre retrospective analysis on growth of residual hepatocellular adenoma after resection

Abstract: Background & Aims Hepatocellular adenoma (HCA) is a benign liver tumour that may require resection in select cases. The aim of this study was to the assess growth of residual HCA in the remnant liver and to advise on an evidence‐based management strategy. Method This multicentre retrospective cohort study included all patients with HCA who underwent surgery of HCA and had residual HCA in the remnant liver. Growth was defined as an increase of >20% in transverse diameter (RECIST criteria). Data on patient and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…The most common risk factor for developing HCAs in Western countries is by far oestrogen in oral contraceptives (OCs) with the highest rate of use being in European countries 5–7 . Following the discontinuation of OCs, which is now part of the recommended management of HCAs, 8 HCAs may remain stable, regress, grow, or recur 9–14 . HCAs are rare in or after the menopause 15 …”
Section: Risk Factorsmentioning
confidence: 99%
“…The most common risk factor for developing HCAs in Western countries is by far oestrogen in oral contraceptives (OCs) with the highest rate of use being in European countries 5–7 . Following the discontinuation of OCs, which is now part of the recommended management of HCAs, 8 HCAs may remain stable, regress, grow, or recur 9–14 . HCAs are rare in or after the menopause 15 …”
Section: Risk Factorsmentioning
confidence: 99%
“…A retrospective study of 44 patients by Shao et al (10), indicated that lesions with important fat infiltration (characteristic for H-HCA) showed a significant less size decrease after OCP cessation compared to those without fat infiltration. The team of Klompenhouwer et al (13) found a difference for HCA regression in different subtypes, in favour of I-HCA and unclassified HCA, although in a retrospective study of 134 patients no statistically significant differences could be found (12).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, most series included both single and multiple HCAs which complicates the interpretation. An overview of the current literature about the evolution of multiple HCAs and correlation with the different subtypes is presented in table 2 (5,8,(10)(11)(12). Information about the impact of OCP withdrawal on the different subtypes is scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Después de la resección está indicada la vigilancia del adenoma residual, y en caso de crecimiento progresivo se debe reintervenir. (41) Hay casos publicados de CHC que surgen después de adenomas múltiples resecados, considerándose que representan focos de CHC resecados dentro de adenomas. También, se ha publicado la regresión de estos tumores con la suspensión de los esteroides por vía oral.…”
Section: Mecanismos De Transformacion Malignaunclassified